Reflection of Pulse Waves and Resonance - Kizilova, N. (My University, 2002)
The problem of axisymmetric wave flow of a viscous incompressible fluid in a system consisting of a long thin deformable tube and a terminal element that determines the conditions of wave reflection at the tube end is analyzed. An expression for the input admittance of the system is obtained and the dependence of the admittance on the system parameters is investigated. The resonant frequencies at which the admittance amplitude has extrema are found and it is shown that at these frequencies the admittance variations with variation of the terminal-element parameters are maximal. The dependence of the resonant frequency on the tube length is investigated. Possible applications of the results obtained to the hydromechanical interpretation of a novel method of pulse diagnostics are discussed.
Keywords: waves in elastic tubes; pulse diagnostics; input admittance; spectral analysis